A new rhodamine-based chemosensor for turn-on fluorescent detection of Fe3+1. Issue 10 (21st May 2015) - Han, Xiang; Wang, Dong-En; Chen, Sheng; Zhang, Longlong; Guo, Yadan; Wang, Jinyi
<x xml:space="preserve">Abstract</x> A new fluorescent probe RH-Fe was developed as a colorimetric and fluorescent chemosensor for Fe3+.